2020
DOI: 10.1126/sciimmunol.aay2754
|View full text |Cite
|
Sign up to set email alerts
|

Divergent T follicular helper cell requirement for IgA and IgE production to peanut during allergic sensitization

Abstract: Immunoglobulin A (IgA) is the dominant antibody isotype in the gut and has been shown to regulate microbiota. Mucosal IgA is also widely believed to prevent food allergens from penetrating the gut lining. Even though recent work has elucidated how bacteria-reactive IgA is induced, little is known about how IgA to food antigens is regulated. Although IgA is presumed to be induced in a healthy gut at steady state via dietary exposure, our data do not support this premise. We found that daily food exposure only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 86 publications
2
46
0
Order By: Relevance
“…cholera toxin) and help from CD4 + T cells, which does not include Tfh cells or T-follicular regulatory cells. 52 As deficiency of IgA is associated with increased prevalence of atopic disease, 53,54 these findings suggest that intestinal IgA may protect against allergic inflammation.…”
Section: Protective Responses Of Igamentioning
confidence: 96%
See 2 more Smart Citations
“…cholera toxin) and help from CD4 + T cells, which does not include Tfh cells or T-follicular regulatory cells. 52 As deficiency of IgA is associated with increased prevalence of atopic disease, 53,54 these findings suggest that intestinal IgA may protect against allergic inflammation.…”
Section: Protective Responses Of Igamentioning
confidence: 96%
“…Food-specific IgA has been detected at elevated levels in the serum of infants that become allergic later in life, 55 as well as in mice that have been sensitized to peanut plus a mucosal adjuvant. 52 Yet, others have shown that egg white-specific IgA2 is lower in the serum of allergic children than healthy controls, and only children that recover from the allergy show increased egg white-specific IgA2 over time. 56 Furthermore, consumption of an antigen-free diet results in the reduction of both serum IgA and the frequency of food antigen-specific Tregs in the small intestine that are important for driving oral tolerance.…”
Section: Protective Responses Of Igamentioning
confidence: 99%
See 1 more Smart Citation
“…2,9,96,[101][102][103][104] Indeed, Tfh subpopulations have been described both in humans and mice, and these may play distinct roles in mediating humoral responses in allergy and asthma and lead to specific protection following vaccination and infection. 94,102,105,106 In a key study, Eisenbarth and colleagues demonstrated that IL-13-producing Tfh (Tfh13) cells co-express Bcl6 and GATA3 in mice and humans with IgE antibodies against allergens. Tfh13 cells triggered the production of high-affinity IgE, which led to the induction of anaphylaxis.…”
Section: Klf2mentioning
confidence: 99%
“…10,108 This likely acts to maintain identity and function or to generate plasticity between CD4 + effector populations and may mediate the functional heterogeneity within Tfh and Th1 populations throughout infection and disease. 102,105,107 Thus, the integration of and balance between transcription factor instruction with inflammatory mediator signaling is of undeniable interest.…”
Section: Klf2mentioning
confidence: 99%